A review of structural magnetic resonance neuroimaging. Issue 9 (16th August 2004) - Symms, M; Jäger, H R; Schmierer, K; Yousry, T A
Abstract : Magnetic resonance imaging (MRI) is often divided into structural MRI and functional MRI (fMRI). The former is a widely used imaging technique in research as well as in clinical practice. This review describes the more important developments in structural MRI in recent years, including high resolution imaging, T2 relaxation measurement, T2*-weighted imaging, T1 relaxation measurement, magnetisation transfer imaging, and diffusion imaging. The principles underlying these techniques, as well as their use in research and in clinical practice, will be discussed.